Changes in blood serum biochemical indicators in toxocares infested cats with different indicators of invasion intensity - Perviy, A.; Yevstafieva, V. (Scientific Progress & Innovations, 2025)
Toxocariasis in cats is a zoonotic nematode invasion and is dangerous to both cats and humans. During the life cycle, toxocares in the animal's body migrate to various organs and tissues, where they cause pathological changes, such as inflammation of the mucous membrane of the small intestine, stomach, bile ducts of the liver, bronchi. As a result of parasitism, toxocares secrete toxins that, when they enter the blood, cause general intoxication of the animal's body, which is accompanied by changes in hematological and biochemical parameters of blood serum. The aim of the research was to establish the peculirities of changes in biochemical parameters of blood serum of cats infected with Toxocara cati, taking into account the intensity of the invasion. Three groups of animals were formed, one of which was a control one (clinically healthy cats) and two experimental groups (infected with toxocares at different intensities of infestation – 586.9 and 126.3 eggs per gram of feces). The content of total protein, albumins, globulins, total bilirubin, creatinine, glucose, calcium and phosphorus was determined in the blood of cats. It was found that with higher intensity indicators of toxocariasis invasion, the changes in biochemical blood parameters of the diseased cats were more significant compared to the changes registered in cats with lower intensity of toxocariasis invasion. For example, with the invasion intensity of 126.3 eggs/g, a slight decrease (P<0.05) in the blood serum of the diseased cats was found in the content of albumins by 9.07 % and glucose by 12.5 %. The content of total protein, globulins, total bilirubin, creatinine, calcium and phosphorus in the diseased cats was within physiological limits. At an intensity of toxocariasis invasion of 586.9 eggs/g, the even larger decrease (P<0.01) in the content of albumins by 18.94 % and glucose by 19.64 % was detected in the blood serum of the infected cats, as well as the decrease (P<0.05) in the content of calcium by 8.33 % and phosphorus by 18.75 %. At the same time, the content of globulins increases (P<0.05) by 10.48 %, and also total bilirubin by 39.58 % and creatinine by 16.48 %. The obtained research results allow us to understand some aspects of the invasion pathogenesis at different indicators of cats’ infestation and effectively conduct therapeutic measures.